Analisis Naratif Pesan Kejujuran dalam Film Pendek “Benih Kejujuran” pada Kanal YouTube Cerdas Berkarakter Kemendikdasmen RI sebagai Media Digital Public Relations - Efriza Aulia Pasya; Mareta Puri Rahastine; Anggie Ayu Astria Latuperissa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The construction of the message of honesty in the short film “Benih Kejujuran,” produced and published on the YouTube channel Cerdas Berkarakter of the Ministry of Primary and Secondary Education of the Republic of Indonesia (Kemendikdasmen RI), is examined as a form of the government's digital public relations practice. A qualitative descriptive approach, situated within the constructivist paradigm and informed by Walter Fisher's Narrative Paradigm, is employed to analyze the film's textual elements, including scenes, dialogue, characterization, and conflict resolution. The analysis is guided by six indicators derived from the two dimensions of narrative rationality, namely narrative coherence (structural, material, and characterological) and narrative fidelity (values, consequences, and experiential overlap). Data were obtained through non-participant observation, documentation, and an in-depth interview with a film studies expert as supporting evidence, while source triangulation was applied to ensure the validity of the findings. The results demonstrate that the film achieves strong structural coherence through its linear narrative, material coherence through its resemblance to familiar children's moral stories such as Pinocchio and The Empty Pot, and characterological coherence through the consistent depiction of Syamila as an honest character. Regarding narrative fidelity, the film presents honesty as a desirable moral value, illustrates logical social consequences for dishonest behavior, and reflects experiences that closely align with the everyday school life of Indonesian children. These findings suggest that “Benih Kejujuran” demonstrates strong narrative rationality and effectively functions as a digital public relations medium through which Kemendikdasmen RI communicates character education values in a persuasive rather than overtly didactic manner, while also indicating opportunities to strengthen the authenticity of the school environment portrayed in the film.